EFEKTIVITAS SITUS KEJARCITA: MEDIA DAN ASESMEN BELAJAR GRATIS UNTUK SISWA SEKOLAH DASAR [THE EFFECTIVENESS OF KEJARCITA WEBSITE: FREE LEARNING MEDIA AND ASSESSMENT FOR ELEMENTARY SCHOOL STUDENTS] - Samsoedin, Susiana; Suciati, Suciati (Universitas Pelita Harapan, 2023)
AbstractThis research and development study aims to increase the use of websites in learning for elementary school students through free features of video media and learning assessments in the form of question banks and quizzes. The variables studied were the appearance, effectiveness, practicality, and satisfaction of using the features on Kejarcita website. Website revisions were conducted after validation from experts and field trials that involved 349 students and 12 teachers of SD Mahabodhi Vidya and SD Muhammadiyah 6. The expert validation result showed that the website as a learning resource is sufficient. Literacy and numeracy assessments as the indicator of effectiveness are considered quite effective with a percentage of 60% on literacy and 56% on numeracy. The website shows 82% effectiveness from the teacher's side and 81% from the students’ side. The practical results of the website are 77% from the students’ side and 79% from the teachers’ side. The satisfaction shows 79% from the teacher's side. It is concluded Kejarcita website after revision is considered effective, practical and provides user satisfaction.Bahasa Indonesia AbstrakPenelitian pengembangan ini bertujuan untuk meningkatkan penggunaan website untuk pembelajaran anak-anak sekolah dasar dengan menggunakan fitur gratis berupa video dan asesmen dalam bentuk bank soal dan kuis. Variabel yang diteliti adalah tampilan, efektivitas, kepraktisan, dan kepuasan penggunaan fitur pada website Kejarcita. Revisi website dilakukan setelah divalidasi oleh pakar, dan uji coba lapangan melibatkan 349 siswa dan 12 guru SD Mahabodhi Vidya dan SD Muhammadiyah 6. Hasil validasi pakar menunjukkan revisi website sebagai sumber belajar sudah memadai. Asesmen belajar literasi dan numerasi siswa sebagai indikator efektivitas dinilai cukup efektif dengan persentase sebesar 60% pada asesmen literasi dan 56% pada asesmen numerasi. Efektivitas website dari sisi guru sebesar 82% sedangkan dari sisi siswa sebesar 81%. Sedangkan, kepraktisan website sebesar 77% dari sisi siswa dan 79% dari sisi guru. Kepuasan penggunaan website dari sisi guru sebesar 79%. Dapat disimpulkan website Kejarcita pasca revisi dinilai efektif, praktis dan memberikan kepuasan pada pengguna.